ANALISIS PENDAPATAN USAHATANI SALAK DI DESA WERDI AGUNG SELATAN KECAMATAN DUMOGA TENGAH KABUPATEN BOLAANG MONGONDOW (Analysis of Salak Business Income in the of South Werdi Agung Village District of Central Dumoga Bolaang Mongondow Regency) - Yelfita Dampi; Jenny Baroleh; Rine Kaunang (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aims to analyze the income of salak farming in Werdi Agung Selatan Village, Central Dumoga District, Bolaang Mongondow Regency. The research was conducted for three months, from November 2019 to January 2020. The sample was selected using a purposive sampling method, in which 20 farmers were taken as samples from the population of 60 farmers. The results showed that the average income obtained from the salak fruit farming was Rp. 1,713,350, - / month.Keywords : Income, farming, Salak